“La Determinación Impositiva de los contribuyentes en el Estado Ecuatoriano versus el Estado Peruano, para medir la presión fiscal durante el año 2014” - Huilcapi Llango, Martha Cecilia (2016)
Compliance with current tax policy and its constant changes have contributed to the analysis of two relevant points of view, the State as a taxable person or collecting agency of the tax and taxpayers as an active subject, through the identification of more tax burden, establish which of these two countries has increased tax burden in the period and the description of the socio-economic situation due to the collection of taxes and the effects caused by the tax burden. Due to the great importance of the collection of taxes as a source of more relevant in the general budget, in this research project the tax of taxpayers Ecuador versus the Peruvian State will be analyzed to measure tax burden in 2014 by the local variables which will help us to determine which country has a higher tax burden. In the first chapter the frame of reference will be analyzed in which the research problem, problem of the problem, formulation of the problem, questions guidelines, general, specific and detailed objective, justification. The second chapter or theoretical foundation established by the unit I, we will cover the tax assessment in general terms, the tax assessment of taxpayers in Ecuador, factors influencing the tax determination, regime used in Ecuador, major tax ,laws and rules, taxes in Ecuador. Unit II is comprised of the tax assessment of taxpayers in Peru, factors influencing the tax determination regime used in Peru, major tax laws and rules, major taxes in Peru. In unit III we describe the definition of fiscal pressure, factors influencing the calculation of the tax burden, how the tax burden, major fiscal pressures of Latin America are calculated. Unit IV the hypothetical unit, hypothesis, variables and operationalization of the variables are detailed. Chapter III is structured by the method, design, type, level of research, population and sample, techniques and tools for data collection, processing techniques and interpretation of data, comparison of the main taxes affecting the determination tax taxpayers Ecuadorian State versus the Peruvian State, study of the economic situation in Ecuador and Peru, effects caused by tax burden and analysis of the tax burden in Ecuador and Peru. Finally conclusions and recommendations will be presented.